Analisis Komparatif Pengalaman Siswa Dalam Evaluasi Pembelajaran Pai Berbasis Konvensional Dan Quizizz - Ach. Syaikhonul Arifin; Abd. Muqit (TADARUS, 2025)
Evaluation of Islamic Religious Education (PAI) learning through conventional methods is often considered monotonous and anxiety-inducing, potentially reducing learning motivation and the validity of the evaluation results themselves. Although digital platforms such as Quizizz have been quantitatively proven to increase learning interest, there remains a gap in in-depth qualitative research on how students socio-affectively interpret and experience the differences between these two methods. This study aims to explore comparatively the emotional and cognitive experiences of students in taking PAI evaluations using conventional methods (written essay exams) and the gamified Quizizz platform. This research employs a descriptive- exploratory qualitative method at SMA Negeri 2 Sidoarjo with students from class X-5 as subjects. Data collection was conducted through in-depth interviews, observations, and documentation, then analyzed using the Miles and Huberman model. The research findings indicate that conventional methods trigger negative emotional responses (tension and pressure) that can hinder students' cognitive performance. Conversely, Quizizz creates positive experiences (enjoyable) that reframe evaluation from a "threat" to a "challenge." This study concludes that the validity of conventional evaluation can be compromised by the psychological burden it creates. Therefore, it is recommended to implement a Blended Assessment Framework that integrates Quizizz for motivating formative assessment and modified conventional methods for summative assessment to measure higher-order thinking skills more effectively and humanely.